DNA MICROARRAY BASED EXPRESSIONAL PROFILING OF HRPXO DEPENDENT UP-REGULONS IN XANTHOMONAS ORYZAE PV. ORYZAE - So, Byoung Ho; Kim, Jongun; Kang, Hee Wan (International Journal of Biosciences and Biotechnology; Vol 1 No 1 (2012))
Thirty-mer oligonucleotides for microarray analysis were designed from the annotated open reading frames(ORFs) in the whole genome sequence of X. oryzae pv. oryzae KACC10331. Mutant hrpXo::TN and wild-typestrain KACC10859 were cultured in hrp inducing medium (XOM2), and cDNAs, which were synthesizedfrom the total RNA samples from both strains, were hybridized on a DNA microarray. The microarraydata showed that 210 genes were down-regulated more than 2-fold in hrpXo::TN, while 115 genes wereup-regulated more than 2-fold. The HrpXo regulons diff erently included 54 hypothetical genes: type IIIsecretory genes (11 hrp genes); genes encoding type III secretory eff ectors (xopP genes and avr/pthA); genesencoding type II secretory eff ectors (6 proteases, a lipase, a polygalacturonase, and 4 cellulases); 7 iron-uptakegenes; 6 pil genes encoding fi mbrial assembly membrane proteins; and 14 transposon genes. Signifi cantplant-inducible promoter (PIP) sequences were newly identifi ed on HrpXo regulons. The validity of theexpressional profi les was further confi rmed by reverse transcription (RT)-PCR.
Keywords: DNA microarray, Xanthomonas oryzae pv. oryzae (Xoo),